Lung Nodule and Functional Changes in Smokers After Smoking Cessation Short-Term Treatment. (14th September 2014) - Maci, Eliana; Comito, Francesca; Frezza, Anna Maria; Tonini, Giuseppe; Pezzuto, Aldo
<x xml:space="preserve">Abstract</x> Background: Tobacco smoke causes lung disfunction and inflammation. Methods: Twenty-two consecutive smokers with undetermined lung nodules were included. All underwent a baseline imaging, exhaled carbon monoxide level evaluation and spirometry, repeated at three months from smoking cessation therapy. Results: A significant reduction in size of the lung nodules was reported (p = .037) as a trend in number reduction (p = .11). A significant increase in blood arterial oxygen pressure (p < .0001), heart rate reduction (p < .01), and FEV1 increase (p < .0001) was recorded. Conclusions: Smoking cessation reduces number and size of lung nodules and improves in lung functionality.